EQUALIZED METHOD: A NEW METHOD TO OPTIMIZE GAS LIFT SPACING DESIGN - Perwira Indro, Axel
In gas lift valve spacing design, there is a common misconception where killing fluid is represented as static no matter the state of the well’s depletion. Killing fluid level, however, changes over time due to fluid infiltration into the reservoir. An innovative method is proposed to optimize gas lift design by considering fluid infiltration movement into the reservoir. The new method is highly effective in depleted reservoirs, where spaces to accommodate the killing fluid entrance are abundant. This paper presents the equalized method as a solution to optimize gas lift valve spacing design. The authors derived an equation based on Darcy’s law and hydrostatic equation to modify the starting depth, at which the equalized condition is reached. The equalized condition is reached when killing fluid movement has reached its final static depth, after a period of time. A case study of Well X, which targets a depleted reservoir, is included to serve as verification to the model. A gas lift system is necessary to maintain oil production in Well X. Using a fixed compressor pressure, conventional gas lift valve spacing design requires a total of eight unloader valves. In contrast, by implementing the equalized method, the number of unloader valves required can be reduced significantly to a total of four valves. The reduction of valves results in higher gas lift operating pressure, higher gas injection passage, and ultimately higher oil production rate obtained compared to conventional design method. This paper presents an optimized gas lift spacing design using the equalized method. The equalized method alters spacing design starting depth using reservoir parameters, well data, and other supporting data. For further application, equalized method can be applied in most gas lift system cases, for a better economic profit.